Conservation of Bats in Florida - Holly K. Ober; Frank J. Mazzotti (EDIS)
WEC-247, a 4-page illustrated fact sheet by Holly K. Ober and Frank J. Mazzotti, aims to dispel fears about bats and describe their benefits. It provides facts about bats and their habitats and how individuals can promote bat conservation. Includes additional sources of information. Published by the UF Department of Wildlife Ecology and Conservation, August 2008.